(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The paper presents an approach of researches effective organization in sphere of operational IT risk governance. For this purpose, the application of digital multilanguage research area is advised, which can simplify discussion processes for users/researchers from different countries. The concept of multilanguage website is developed based on performed analysis of following modern IT application trends of website development: Web 2.0., social networks, blogs, wiki, etc. Then, practical solutions of advised concept realization are discussed. The presented concept is developed within the project, which is devoted to the research of operational IT risk governance in monetary and financial institutions. Still, the advised concept can be easily adapted for other research areas